Correction: MurCSS: A Tool for Standardized Evaluation of Decadal Hindcast Systems. Issue 1 (24th June 2016) - Illing, Sebastian; Kadow, Christopher; Kunst, Oliver; Cubasch, Ulrich
This article details a correction to the article: Illing S, Kadow C, Oliver K, Cubasch U. MurCSS: A Tool for Standardized Evaluation of Decadal Hindcast Systems. Journal of Open Research Software. 2014; 2(1): e24. DOI:http://doi.org/10.5334/jors.bf